Investigating the Impact of Teacher Enthusiasm on Engagement Among Saudi First-Year EFL Students - Saeed Alghamdi , Maram; Abdulrhamn Khadawardi, Hanadi (International Journal of English Language Education, 2024)
This study examines the influence of teacher enthusiasm (TE) on student engagement in English as a foreign language (EFL) classroom in Saudi Arabia. Specifically, it explores the relationships between students’ perceptions of TE and their levels of engagement, as well as the teaching methods that lead students to perceive their teachers as enthusiastic and the challenges teachers face in maintaining enthusiasm from the student perspectives. A mixed method approach was employed, involving questionnaires distributed to 202 primary year students and semi-structured interviews were conducted with 2 students. The quantitative findings revealed a significant positive correlation between TE and SE. The findings revealed that students perceived certain teaching methods as contributing to teacher enthusiasm, such as varying vocal tones, positive reinforcement, active movement in the classroom, incorporating interactive activities and discussions, and relating content to personal interests. When teachers lacked these enthusiastic methods, students reported a less engaging classroom experience characterized by monotony. Moreover, students reveal key challenges impeding TE which included workload, emotional distress, class timing, and lack of interest from some students. Based on these findings, the study offers practical recommendations for promoting student-centered pedagogy to enhance enthusiasm among EFL teachers and engagement among learners.